Mediating role of intrinsic motivation in relationship between perception of organizational justice and extra-role behaviors among Wasit University faculty members - Abdulridha Hussein Shihmani, Hayder; Manshaee, Gholamreza; Marid Jabur, Adnan; Mahdad, Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to analyze the mediating role of intrinsic job motivation in relationship between perception of organizational justice and extra-role behaviors of faculty members of Wasit University in Iraq. Methodology: Research method was Correlation and statistical population included all faculty members of Wasit University in the spring and summer of 1403 (summer of 2024). 250 people were selected from mentioned statistical population through convenience sampling method, and answered to three questionnaires of extra-role behaviors (Lee and Allen, 2002), perception of organizational justice (Colquitt, 2001), and internal job motivation (Gagne et al. 2015). Research data were analyzed using Pearson’s correlation coefficient and Structural Equation Modeling (SEM) by using SPSS version 26 and AMOS version 25. Findings: The results showed that the perception of organizational justice has a significant relationship with internal job motivation and extra-role behaviors (p<0.01). Moreover, the results of structural equation modeling showed that intrinsic job motivation is a complete mediating variable in the relationship between the perception of organizational justice and extra-role behaviors. Conclusion: Based on the findings of the present study, it is necessary to implement and develop fair policies in distributive, procedural and interactive fields in order to develop extra-role behaviors and internal job motivation of university faculty members in academic settings. It should be considered by policymakers of higher education system in Iraq.